Lutra sumatrana Brisson 1762 - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
35. Hairy-nosed Otter Lutra sumatrana French: Loutre de Sumatra / German: Haarnasen-Otter / Spanish: Nutria indonesia Taxonomy. Barangia sumatrana Gray, 1865, Sumatra. Monotypic. Distribution. Mainland SE Asia in Myanmar, Cambodia, Vietnam, and PeninsularMalaysia; also Borneo and Sumatra. Descriptive notes. Head-body 50-82 cm, tail 37.5-50 cm; weight 3.5-6 kg, adult males are larger than females. The Hairy-nosed Otter is small, with a dark brown pelage and paler undersides. The upper lip, sides of the face, chin, and throat are white. The rhinarium is covered with hair, with only the upper edge and margins of the nostrils naked. The limbs are short and strong, the feet are fully webbed and clawed, and the tail is flat dorso-ventrally. The skull is flat but strongly built. Habitat. Coastal wetlands, peat swamps, swamps, large rivers, lakes, and mountain streams. Food and Feeding. The dietis said to be primarily fish, but also includes snakes, frogs, small mammals, crabs, and insects. Activity patterns. Reported to be nocturnal. Movements, Home range and Social organization. Nothing known. Breeding. Nothing known. Status and Conservation. CITES Appendix II. Classified as Endangered in The [UCN Red List. The Hairy-nosed Otteris the rarest and least known among the five species of otters occurring in Asia. Once believed to be extinct, it has been rediscovered in different parts of South-east Asia such as Cambodia (Tonle Sap wetlands), Malaysia (Terengganu and Maur), Sumatra, Thailand (Phru Toa Daeng Peat Swamp Forest), and Viet Nam (U Minh Thuong Nature Reserve in Mekong Delta). Historically it has also been reported from Brunei, Myanmar, and Penang Island. Very little is known about the Hairy-nosed Otter, but it is likely that it is threatened by destruction of peat swamp forests for logging and agriculture. Research is critically needed on all aspects of this species’ ecology and biology. Bibliography. Banks (1949), Francis (2008), IUCN (2008), Lekagul & McNeely (1991), Medway (1969), Nguyen et al. (2001), Poole (2003), Sivasothi & Burhanuddin (1994), Tate (1947), Van Zyll de Jong (1972), Wozencraft (2005). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Mustelidae, pp. 564-656 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on page 645, DOI: 10.5281/zenodo.5714044